Absence of Subcerebral Projection Neurons Is Beneficial in a Mouse Model of Amyotrophic Lateral Sclerosis. Issue 4 (11th July 2020) - Burg, Thibaut; Bichara, Charlotte; Scekic‐Zahirovic, Jelena; Fischer, Mathieu; Stuart‐Lopez, Geoffrey; Brunet, Aurore; Lefebvre, François; Cordero‐Erausquin, Matilde; Rouaux, Caroline
Abstract : Objective: Recent studies carried out on amyotrophic lateral sclerosis patients suggest that the disease might initiate in the motor cortex and spread to its targets along the corticofugal tracts. In this study, we aimed to test the corticofugal hypothesis of amyotrophic lateral sclerosis experimentally. Methods: Sod1 G86R and Fezf2 knockout mouse lines were crossed to generate a model that expresses a mutant of the murine Sod1 gene ubiquitously, a condition sufficient to induce progressive motor symptoms and premature death, but genetically lacks corticospinal neurons and other subcerebral projection neurons, one of the main populations of corticofugal neurons. Disease onset and survival were recorded, and weight and motor behavior were followed longitudinally. Hyper‐reflexia and spasticity were monitored using electromyographic recordings. Neurodegeneration and gliosis were assessed by histological techniques. Results: Absence of subcerebral projection neurons delayed disease onset, reduced weight loss and motor impairment, and increased survival without modifying disease duration. Absence of corticospinal neurons also limited presymptomatic hyper‐reflexia, a typical component of the upper motoneuron syndrome. Interpretation: Major corticofugal tracts are crucial to the onset and progression of amyotrophic lateral sclerosis. In the context of the disease, subcerebral projection neurons might carry detrimental signals to their downstream targets. In its entirety, this study provides the first experimental arguments in favor of the corticofugal hypothesis of amyotrophic lateral sclerosis. ANN NEUROL 2020;88:688–702